Childhood emotional abuse and problematic social networking sites use in a sample of Italian adolescents: The mediating role of deficiencies in self‐other differentiation and uncertain reflective functioning. Issue 7 (10th April 2021) - Musetti, Alessandro; Starcevic, Vladan; Boursier, Valentina; Corsano, Paola; Billieux, Joël; Schimmenti, Adriano
Abstract: Objective: Childhood emotional abuse (CEA) is associated with various negative mental health outcomes. This study aimed to investigate the association between CEA and problematic social networking site (SNS) use in a sample of Italian adolescents. Design: Using structural equation modeling, the study examined whether the relationship between CEA and problematic SNS use was sequentially mediated by self‐other differentiation and uncertain reflective functioning in 1308 Italian adolescents (628 males, age range 13–19 years). Results: A history of CEA was positively associated with problematic SNS use. Furthermore, deficiencies in self‐other differentiation and uncertain reflective functioning partially mediated the relationship between CEA and problematic SNS use. Conclusions: The present study provides additional insight into the psychological dynamics underpinning problematic SNS use among adolescents. The clinical implications of these findings are discussed.